Fibrinogen-based cell and spheroid sheets manipulating and delivery for mouse hindlimb ischemia. (1st April 2023) - Lim, Juhan; Lee, Min Suk; Jeon, Jin; Yang, Hee Seok
Abstract: In this research, we introduced a novel strategy for fabricating cell sheets (CSs) prepared by simply adding a fibrinogen solution to growth medium without using any synthetic polymers or chemical agents. We confirmed that the fibrinogen-based CS could be modified for target tissue regardless of size, shape, and cell types. Also, fibrinogen-based CSs were versatile and could be used to form three-dimensional (3D) CSs such as multi-layered CSs and those mimicking native blood vessels. We also prepared fibrinogen-based spheroid sheets for the treatment of ischemic disease. The fibrinogen-based spheroid sheets had much higher in vitro tubule formation and released more angiogenic factors compared to other types of platform in this research. We transplanted fibrinogen-based spheroid sheets into a mouse hindlimb ischemia model and found that fibrinogen-based spheroid sheets showed significantly improved physiological function and blood perfusion rates compared to the other types of platform in this research.